Periodic boundary conditions for the simulation of uniaxial extensional flow of arbitrary duration. Issue 5 (23rd March 2016) - Hunt, Thomas A.
Abstract : It is very common with molecular dynamics and other simulation techniques to apply Lees–Edwards periodic boundary conditions (PBCs) for the simulation of shear flow. However, the behaviour of a complex liquid can be quite different under extensional flow. Simple deformation of a simulation cell and its periodic images only allows for simulations of these flows with short duration. For the simulation of planar extensional flow, it was recognised that the PBCs of Kraynik and Reinelt [Int. J. Multiphase Flow 1992;18:1045] could be used to perform simulations of this flow with arbitrary duration. However, a very common extensional flow in industrial applications and experiment is uniaxial extensional flow. Kraynik and Reinelt found that their method could not be directly generalised to this flow because of the lack of a lattice which reproduces itself during uniaxial extension. PBCs are presented in this article, which avoid this problem by finding a lattice which is compatible with the flow, finding the reduced basis to the lattice at all times and using this basis when calculating the position and separation of particles. Using these new PBCs, we perform nonequilibrium molecular dynamics simulations of a simple liquid and show that the technique gives results which agree with those from simulations using simply deforming PBCs.